Usuárias do centro de práticas integrativas e complementares: despertando para o cuidar de si - Cordeiro, Camila Abrantes (2015)
The change of the attention to mental health model within the NHS is directed to the expansion of health care practices that seek to include and integrate the different subject areas of society, implementing care technologies in order to promote health promotion and prevention of illness mental. In this sense, the Caring for the Caregiver / Rescue Self-esteem acts as a light care technology that provides a forum for support, speaking and listening, which in turn enables its members to redeem their self-esteem, helping them to face and overcome the difficulties of everyday life. This research aimed to: identify care practices offered by care spaces that arouse in the users the desire to care for themselves; investigate the motivation of health professionals about the development of workshops with community care. It is a comprehensive research of qualitative-interpretative approach to the study of which was used thematic oral history as a methodological way. The setting of the research was the center of Integrative and Complementary Practices - Balance of Being and the Center for Comprehensive Care Health, located in the city of João Pessoa - PB.O empirical data were obtained through interviews with ten employees and the analysis of this material was performed based on the thematic analysis proposed by Minayo, which enabled the construction of the thematic axes: I - Relationship care of themselves and each other: awakening to resilience; II - Workshops taking care of the caregiver / redemption of self-esteem, motivation of health workers. The speeches of the collaborators revealed significant changes in personal and professional context in which it was revealed that the workshops of care made possible the rescue of self-esteem, awakening to the resilience, the look itself from the self, reinforcing the concept of autonomy, contributing to the (re) signification of his life story, his sufferings. The process of change observed from the inclusion of these individuals in the workshops of care, fostered a better understanding of self and other, recognizing the dialectical relationship of care and also contribute to the establishment and strengthening of bonds. We conclude therefore, that taking care of the caregiver / redemption of self-esteem corroborates with the principles of the NHS, encouraging the implementation and consolidation of new care practices that enhance health promotion, prevention and restoration of health of individuals, families and communities so integral.